The structure of the γ-TuRC: a 25-years-old molecular puzzle - Župa, Erik; Liu, Peng; Würtz, Martin; Schiebel, Elmar; Pfeffer, Stefan (Current opinion in structural biology, 2021)
The nucleation of microtubules from αβ-tubulin dimers is an essential cellular process dependent on γ-tubulin complexes. Mechanistic understanding of the nucleation reaction was hampered by the lack of γ-tubulin complex structures at sufficiently high resolution. The recent technical developments in cryo-electron microscopy have allowed resolving the vertebrate γ-tubulin ring complex (γ-TuRC) structure at near-atomic resolution. These studies clarified the arrangement and stoichiometry of gamma-tubulin complex proteins in the γ-TuRC, characterized the surprisingly versatile integration of the small proteins MZT1/2 into the complex, and identified actin as an integral component of the γ-TuRC. In this review, we summarize the structural insights into the molecular architecture, the assembly pathway, and the regulation of the microtubule nucleation reaction.